2018
DOI: 10.1177/0954405418755822
|View full text |Cite
|
Sign up to set email alerts
|

Achieving maximum dimensional accuracy and surface quality at the shortest possible time in single-point incremental forming via multi-objective optimization

Abstract: Single-point incremental forming is a novel and flexible method for producing three-dimensional parts from metal sheets. Although single-point incremental forming is a suitable method for rapid prototyping of sheet metal components, there are limitations and challenges facing the commercialization of this process. Dimensional accuracy, surface quality, and production time are of vital importance in any manufacturing process. The present study is aimed at selecting proper forming parameters to produce sheet met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…It was found that the tool head diameter had the most significant effect on the geometric accuracy. Abolfazl Taherkhani et al [11] used the group method of data handling (GMDH), an artificial neural network to model the relationships between tool head diameter, layer spacing, sheet thickness, feed speed, axial accuracy, and surface quality. The model was validated by experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the tool head diameter had the most significant effect on the geometric accuracy. Abolfazl Taherkhani et al [11] used the group method of data handling (GMDH), an artificial neural network to model the relationships between tool head diameter, layer spacing, sheet thickness, feed speed, axial accuracy, and surface quality. The model was validated by experiments.…”
Section: Introductionmentioning
confidence: 99%
“…L 16 Taguchi orthogonal array is adopted to investigate how the four input variables affect the SR of the mild steel sheets. The control factor values for each SPIF experiment are shown in Table 3.…”
Section: -Resultsmentioning
confidence: 99%
“…The results illustrated that the most important parameter that influenced the surface roughness was the step down. Taherkhani et al [16], using the Al3105 sheets, performed four process parameters to model the Group Method of Data Handling (GMDH) as a sub model of artificial neural networks.…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the die design and optimization, the metamodeling and optimization methods, which are also called as surrogate-assisted optimization, have been extensively applied in laboratories and industries due to the high efficiency and feasibility in dealing with the strong nonlinear, high-dimensional and large-scale metal forming problems. 46 Zhao performed a multi-objective optimization for porthole extrusion die based on Kriging metamodeling and Pareto-based genetic algorithm (GA) to decrease the die stress and mandrel deflection and even the velocity distribution in the cross section of the profile. 7 Sun 8 investigated the effects of geometry of second-step welding chamber of the extrusion die on the standard deviation of the velocity field in bearing exit and obtained the optimum parameter set by combining Box–Behnken experimental design with response surface method.…”
Section: Introductionmentioning
confidence: 99%